Dust storms ahead: Climate change, green energy development and endangered species in the Mojave Desert. (January 2023) - Smith, Christopher Irwin; Sweet, Lynn C.; Yoder, Jeremy; McKain, Michael R.; Heyduk, Karolina; Barrows, Cameron
Abstract: The Mojave Desert contains the hottest, driest regions in North America and is also one of the most ecologically intact regions in the contiguous United States. However, a confluence of factors including urbanization, climate change, and energy development are rapidly transforming this ecoregion. As a result of these growing threats, even common, widespread Mojave Desert endemics are at risk of being driven to extinction by the end of the 21st century. Ironically, renewable energy development that could delay or even reverse the effects of climate change in the region is also a potentially significant source of habitat loss for these same organisms. Protecting the Mojave therefore presents difficult choices about how to select among different conservation priorities. We argue that these choices will necessarily involve compromises in which protections for some habitats will have to be prioritized while allowing development in other areas. We review the state of conservation in the Mojave and use the Mojave Desert's iconic Joshua trees ( Yucca brevifolia and Y. jaegeriana ) as a case study to describe a framework for identifying habitats that should be given the highest levels of protection to ensure climate change resilience. Finally, using existing spatial data, we evaluate land use and conservation status in the Mojave. The result identifies considerable scope for compromise between conservation and renewable energy development. Although our examples are specific to the Mojave, we argue that these recommendations apply broadly to many biological communities threatened by climate change. Highlights: Climate change is a global threat that reduces biodiversity. Renewable energy offers a potential solution, but also impacts biodiversity. The Mojave Desert is threatened by climate change, and energy development. Joshua trees offer a case study of conflicting conservation goals. Recommendations for prioritizing conservation in the Mojave are offered.